Identification of Human Papilloma Viruses in Atheromatous Coronary Artery Disease - Lawson, James S.; Glenn, Wendy K.; Tran, Dinh D.; Ngan, Christopher C.; Duflou, Johan A.; Whitaker, Noel J. (Frontiers in Cardiovascular Medicine, 2015)
Objective. To identify human papilloma viruses (HPV) in atheromatous coronary arteries. Background. Atheromatous arterial disease is primarily an initial inflammatory response to unknown stimuli. The crucial question is “what causes the initial inflammation in atheromatous disease?” HPV infections may be relevant as US women with vaginal, high risk for cancer, HPV infections, are at up to three fold increased risk of cardiovascular disease as compared with vaginal HPV negative women. These studies did not include analyses of HPV in atheromatous coronary arteries. Methods. Atheromatous coronary arteries were identified and collected from 20 deceased donors. PCR techniques were used to identify HPV gene sequences. Immunohistochemistry methods were used to identify HPV E7 proteins. Results. HPV types 16 and 18 were identified in 11 (55%) of 20 specimens. HPV E7 protein was identified in 10 (50%) of 20 specimens. Positive and negative HPV identification and HPV E7 expression in coronary smooth muscle cells were significantly correlated (cc = 0.503, p = 0.024). The HPV E7 proteins were expressed in smooth muscle cells and plasma cells, foam cells and macrophages located in the atheromatous plaque. HPV E7 proteins were not expressed in infiltrating lymph cells. Conclusions. HPV gene sequences were identified in 55% of atheromatous coronary arteries and may have a role in coronary artery disease.